An edible cutleries using green materials: sorghum flour - Kabir, Mohd Hafizalrisman; Hamidon, Nuramidah; Awang, Mariah; Abdul Rahman, Mohammad Ashraf; Adnan, Suraya Hani (Springer Link, 2022)
Plastic cutlery may be a convenient alternative and detrimental to the health. The presence of toxins and carcinogens that can quickly be ingested into the body is a petroleum by-product. As toxins and carcinogens can leech into food through the natural ecosystem, the processing of plastic cutlery has become harmful for the environment. Therefore, to minimize the negative impact towards the environment, and to support the green materials product, this study proposes an edible cutlery from sorghum flour. This study aims to calculate the exact quantity of the product used to manufacture edible cutlery, to identify the expense of making edible cutlery, and to compare the ability of edible cutleries and plastic cutleries to resist water absorption test and soil burial test. The edible cutleries are produced from the combination of natural ingredients like green materials, which are sorghum flour, wheat flour and rice. The tests involved in this study are soil burial test and water absorption test. Thus, from this study, it can minimize the negative impact towards the environment and be able to replace the conventional plastic cutleries. For commercialized purposes in future, the edible cutlery should be moulded in perfect shape and size to get the same quality for every single unit.